Economic Policy in a Liberalising Economy Indian Reform in this Century - Alagh, Yoginder Kumar (SpringerBriefs in Economics,, 2018)
This book follows up on the author's popular previous volume on Indian development planning and policy, published under the UNU WIDER series in development economics. It first introduces an evaluation of the newly mandated policy body of India, National Institution for Transforming India (also called the NITI Aayog), which replaced the erstwhile Planning Commission. As per the government site, NITI Aayog is the premier policy 'Think Tank' of the Government of India, providing both directional and policy inputs. While designing strategic and long term policies and programmes for the Government of India, NITI Aayog also provides relevant technical advice to the Centre and States.The book goes on to critically describe and analyse the think tank's policies in sectors like population, demographics and poverty; agriculture and industry; and infrastructure. Lastly, the concluding chapter discusses appropriate future policies. The approach is to analyse the policy stance of the present Government in India as stated in recent official documents and to see if it has any relationship with past plans in terms of concepts or program details. In addition to the policy makers, the book is a must have resource for students of development economics, particularly of India, and provides a critical account of policies for emerging economies. .